CORPORATE GOVERNANCE DYNAMICS IN DIGITAL PUBLIC SERVICE POLICY IMPLEMENTATION: A CASE STUDY OF BANDUNG INTEGRATED MANPOWER MANAGEMENT APPLICATION - Theresa Shinta Ajie; Budiman Rusli; Herijanto Bekti (DIA: Jurnal Administrasi Publik, 2026)
This study aims to analyze the influence of corporate governance dynamics on the implementation of digital public service policies through the Bandung Integrated Manpower Management Application (BIMMA) in the city of Bandung. This research uses a qualitative approach with a case study design, focusing on one main dimension, namely the dynamics of digital governance which is analyzed through aspects of organizational structure and finance, organizational governance, organizational policies, and decision-making. The results of the study show that the implementation of BIMMA has not fully functioned as a strategic instrument for public service transformation. Hierarchical organizational structures, limited long-term budget support, weak institutionalization of digital governance, lack of operational internal policies, and decision-making patterns that are still bureaucratic and reactive are the main factors inhibiting the effectiveness of digital services. These findings strengthen the framework of corporate governance dynamics by emphasizing that the success of public service digital policies is largely determined by organizational governance capacity, not solely by technological readiness.